1978
DOI: 10.1258/002367778781088585
|View full text |Cite
|
Sign up to set email alerts
|

Volvulus at the i1eocaecal junction in germfree mice

Abstract: 16 cases of intestinal volvulus were observed in a total of 200 inbred C57BL/6N, GR/N, and DBA/2N germfree mice during the course of 2 years. The volvulus was a twisting of the caecum at the junction of the ileum, caecum and colon, resulting in occlusion and death. In each case the caecum was greatly enlarged. During the same period no intestinal volvulus was seen in 5 other germfree strains or in F1 to F4 generations of identical strains of microflora-associated and conventionalized mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The high death rate observed in the early colonies of GF animals led to realization that commensal microorganisms in the intestine produce essential nutrients such as vitamins K and B. Supplementation of the diet with essential components extended the lifespan of GF animals to that of conventionally raised ones (2). Yet, sudden death due to cecal volvulus is not uncommon (4), and the average body weight and fat tissue volume tend to be smaller in some strains of GF animals compared to conventional animals (5). These observations suggest that although commensal microorganisms are not required for mammalian development, they provide essential nutrients and assist in digestion.…”
Section: Introductionmentioning
confidence: 99%
“…The high death rate observed in the early colonies of GF animals led to realization that commensal microorganisms in the intestine produce essential nutrients such as vitamins K and B. Supplementation of the diet with essential components extended the lifespan of GF animals to that of conventionally raised ones (2). Yet, sudden death due to cecal volvulus is not uncommon (4), and the average body weight and fat tissue volume tend to be smaller in some strains of GF animals compared to conventional animals (5). These observations suggest that although commensal microorganisms are not required for mammalian development, they provide essential nutrients and assist in digestion.…”
Section: Introductionmentioning
confidence: 99%
“…However, a greatly enlarged cecum can cause health issues in aged GF animals. Cecal torsion due to a greatly enlarged cecum was described as the major health issue in aged GF animals [ 20 , 24 ]. Using two aging cohorts, we showed that the expected lifespan of GF B6J is shorter than that of GF C3H mice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the cecal size in GF rodents increases with age [ 16 ]. Greatly increased cecum can promote cecal torsion causing obstruction of the digestive tract followed by the partial constriction of the blood supply and the death of the animal with or without previous clinical symptoms such as abdominal distension, lack of feces, ragged fur, hypoactivity, and ataxia [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%